A randomized half-body, double blind, controlled trial on the effects of a pH-modified moisturizer vs. standard moisturizer in mild to moderate atopic dermatitis, - Siew Wen Goh; Adawiyah Jamil; Nazarudin Safian; Norazirah Md Nor; Norliza Muhammad; Nur Liyana Saharudin (Sociedade Brasileira de Dermatologia, 2020)
Abstract Background: Higher skin pH in atopic dermatitis contributes to impaired epidermal barrier. A moisturizer compatible with physiological pH could improve atopic dermatitis. Objective: To determine the effect of a physiologically compatible pH moisturizer in atopic dermatitis. Methods: A randomized half body, double blind, controlled trial involving patients with stable atopic dermatitis was performed. pH-modified moisturizer and standard moisturizer were applied to half body for 6 weeks. Results: A total of 6 (16.7%) males and 30 (83.3%) females participated. Skin pH reductions from week 0, week 2 and 6 were significant at the forearms (5.315 [0.98] to 4.85 [0.54] to 5.04 [0.78], p = 0.02) and abdomen (5.25 [1.01], 4.82 [0.64], 5.01 [0.59], p = 0.00) but not at the shins (5.01 [0.80], 4.76 [0.49], 4.85 [0.79], p = 0.09) with pH-modified moisturizer. Transepidermal water loss (TEWL) at the forearms decreased (4.60 [2.55] to 3.70 [3.10] to 3.00 [3.55], p = 0.00), abdomen (3.90 [2.90] to 2.40 [3.45] to 2.70 [2.25], p = 0.046). SCORAD improved from 14.1 ± 12.75 to 10.5 ± 13.25 to 7 ± 12.25, p = 0.00. In standard moisturizer group, pH reductions were significant at the forearms (5.29 [0.94] to 4.84 [0.55] to 5.02 [0.70], p = 0.00) and abdomen (5.25 [1.09], 4.91 [0.63], 5.12 [0.66], p = 0.00). TEWL at the forearm were (4.80 [2.95], 4.10 [2.15], 4.60 [3.40], p = 0.67), shins (3.80 [1.40], 3.50 [2.35], 4.00 [2.50], p = 0.91) and abdomen (3.70 [2.45], 4.10 [3.60], 3.40 [2.95], p = 0.80). SCORAD improved from 14.2 ± 9.1 to 10.9 ± 10.65 to 10.5 ± 11, p = 0.00. Reduction in pH was observed with both moisturizers while TEWL significantly improved with pH-modified moisturizer. pH-modified moisturizer resulted in greater pH, TEWL and SCORAD improvements however the differences were not significant from standard moisturizer. Study limitation: Skin hydration was not evaluated. Conclusion: Moisturization is beneficial for atopic dermatitis; use of physiologically compatible pH moisturizer is promising.